2000
DOI: 10.1037/0735-7044.114.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala lesions do not impair shock-probe avoidance retention performance.

Abstract: The author has granted a non-L'auteur a accordé une The present experiment used the shock-probe paradigm, a procedure usually used to assess anxiolytic processes, to assess memory in amygdala-lesioned rats. Rats were placed in a chamber that contained a probe protmding from 1 of 4 walls and were kcpt in the chamber for 15 min after they contacted the probe. For half the rats, the probe was electrified (2 mA). Four days later, sham or neurotoxic arnygdala lesions were induced. Retention performance kvas asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
3
23
2
Order By: Relevance
“…However, ive have found that for both sharn and amygdala-lesioned rats, the effect of preoperative shock experience on postoperative shock-probe avoidance is context-dependent. Specifically, unlike the present findings, the postoperative shock-probe avoidance of amygdala-lesioned rats given preoperative shock experience in a standard one-tria1 inhibitoty avoidance paradigm is not different from that of shock-naive rats (Lehmann, Treit, & Parent, 1999). Thus, the most feasible interpretation of the present findings is that amygdalalesioned animals remembered their previous shock experience and that the shockprobe avoidance paradigm permits the expression of the memory.…”
Section: Discussioncontrasting
confidence: 54%
“…However, ive have found that for both sharn and amygdala-lesioned rats, the effect of preoperative shock experience on postoperative shock-probe avoidance is context-dependent. Specifically, unlike the present findings, the postoperative shock-probe avoidance of amygdala-lesioned rats given preoperative shock experience in a standard one-tria1 inhibitoty avoidance paradigm is not different from that of shock-naive rats (Lehmann, Treit, & Parent, 1999). Thus, the most feasible interpretation of the present findings is that amygdalalesioned animals remembered their previous shock experience and that the shockprobe avoidance paradigm permits the expression of the memory.…”
Section: Discussioncontrasting
confidence: 54%
“…Extensive evidence indicates that the amygdala is involved in the learning and memory of conditioned fear. For instance, amygdala lesions may induce anterograde and retrograde amnesia for instrumental and Pavlovian fear conditioning (Liang et al 1982;Dunn and Everitt 1988;Phillips and LeDoux 1992;Sananes and Davis 1992;Kim and Davis 1993;Parent et al 1995a;LaBar and LeDoux 1996;Lee et al 1996;Maren et al 1996;Bermudez-Rattoni et al 1997;Muller et al 1997;Maren 1998Maren , 1999Poremba and Gabriel 1999;Wilensky et al 1999;Antoniadis and McDonald 2001).In contrast, other evidence indicates that the amygdala is involved in, but not necessary for the retention of conditioned fear (Vanderwolf et al 1988;Sutherland and McDonald 1990;Helmstetter 1992;Parent et al 1992Parent et al , 1995bHelmstetter and Bellgowan 1994;Killcross et al 1997;Cahill et al 2000;Lehmann et al 2000). For example, we recently demonstrated that the amygdala does not appear to be necessary for retrograde memory for cued fear conditioning (Lehmann et al 2000).…”
mentioning
confidence: 84%
“…In contrast, other evidence indicates that the amygdala is involved in, but not necessary for the retention of conditioned fear (Vanderwolf et al 1988;Sutherland and McDonald 1990;Helmstetter 1992;Parent et al 1992Parent et al , 1995bHelmstetter and Bellgowan 1994;Killcross et al 1997;Cahill et al 2000;Lehmann et al 2000). For example, we recently demonstrated that the amygdala does not appear to be necessary for retrograde memory for cued fear conditioning (Lehmann et al 2000).…”
mentioning
confidence: 85%
“…Increased burying reflects increased anxiety levels, whereas increased probe-contacts or decreased retention latency implicates impaired short-and long-term memory, respectively. The interval between the training and the retention sessions was based on other studies where the retention session of the shock-probe was used to measure aversive memory performance (Lehmann et al, 2000;Shah and Treit, 2003).…”
Section: Introductionmentioning
confidence: 99%